Investigation On Process-Properties Relationship With Load-Bearing Performance Of Lattice-Structured Cellular Material For Lightweight Applications - Hasan, Rafidah; Alkahari, Mohd Rizal; Ismail, Rainah; Said, Radzai; Md Ali, Syaril Azrad; Azmi, Muhamad Syafwan; Rosli, Nur Ameelia (UTeM, 2019)
Lattice structure is a periodic cellular structure which can become lightweight materials with good mechanical properties. This study characterized and examined the manufacturability of lattice structure geometry that was produced by FDM CubePro 3D-printer. The effect of process parameters on ABS lattice-structure's geometry were evaluated and their relationships were derived by using experimental approach. Dynamic behaviour of the material was explored for a better understanding of the material in real applications. The BCC lattice structure specimens were subjected with quasi-static compression and dynamic vibration loadings. Significant process parameter that influenced mechanical performance and geometrical properties for the FDM printer machine was found to be the layer thickness at 200 pm. Vibration test results show that the material's natural frequency was greatly affected by strut diameter sizes due to increase in stiffness as the strut diameter increases. The natural frequency values increase as induced damage location became farthest from clamped edge. With respect to both compression deformation and vibration behaviours of the lattice structure in this study, the material is found to be more suitable in energy absorption applications such as in car engine hood or arm parts of drone due to its bending dominated behaviour when subjected to loading.